Natural convection in a cold enclosure with four hot inner cylinders in a diamond array (Part-II: Effect of unequal horizontal and vertical distances of inner cylinders). (May 2018) - Mun, Gi Su; Seo, Young Min; Park, Yong Gap; Ha, Man Yeong
Highlight: The immersed boundary method was used, based on the finite volume method. Abstract: Two-dimensional numerical simulations were conducted to investigate the natural convection in an enclosure with four cylinders in a diamond array. The convection phenomena induced by the temperature difference between the hot surfaces of the cylinders and enclosure walls were investigated using different Rayleigh numbers (10 3 ≤ Ra ≤ 10 6 ) and distances between neighboring cylinders (0.3 ≤ ε ≤ 0.7). The immersed boundary method (IBM) was used to capture the virtual boundary of the cylinders. Detailed analysis results were obtained using a visualization technique, including the distribution of streamlines and isotherms. The heat transfer characteristics were also investigated with regard to the primary frequency and transition of the flow regime from steady state to unsteady state at a relatively high Rayleigh number of Ra = 10 6 .